Analisis Bakteri Coliform pada Budidaya Ikan Batak (Neolissochilus sumatranus) di Perairan Danau Toba - Herna Febrianty Sianipar; Apriani Sijabat; Christa Voni Roulina Sinaga; Ewin Handoco; Mardame Pangihutan Sinaga; Tambos Sianturi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Batak fish (Neolissochilus sumatranus) is an endemic fish to North Sumatra Province, especially in Lake Toba. Currently, Batak fish are categorized as endangered due to overfishing and their habitat is starting to be damaged, so conservation efforts need to be made, one of which is from microbiological analysis of water found in the aquatic environment in Batak fish farming. This study aims to determine the quality of water in Batak fish farming in terms of aquatic microbiology. This descriptive research was conducted in Lake Toba waters, using random purposive sampling at 4 stations, namely: Parapat, Ajibata, Gorat, and Haranggaol Lake Toba, North Sumatra Province. Microbiological analysis was carried out at the Water Resources Management Laboratory, Faculty of Mathematics and Natural Sciences, University of HKBP Nommensen Pematangsiantar. The results showed that the bacteria found in Batak fish farming in Lake Toba waters were fecal coliform bacteria with numbers at station 1 (360/100 ml), station 2 (830/100 ml), station 3 (1310/100 ml), and station 4 (1110/100 ml). In general, the quality of Batak fish aquaculture water does not meet water quality standards, because the content of fecal coliform bacteria is above the 1000/100 ml quality standard.